Evaluation of flexibility assessment indices upon flexible loading of thermal power plants with high penetration of renewables - Srikanth Reddy Yanala; Matam Sailaja Kumari; Sydulu Maheswarapu; M. Mohana Rao (International Journal of Applied Power Engineering (IJAPE), 2023)
In this paper, power system flexibility assessment indices evaluation has been carried out with high penetration of renewables in MATLAB environment, inspired from IRENA FlexTool. The parameters such as magnitude of energy mix, resources available, electricity tariffs and price affordability play a vital role in the proposed research. The developed program has been tested against IEEE 9 bus and IEEE 39 bus systems with and without time-series data and with and without high penetration of renewables. By closely matching the results for various test cases and time series evaluations for IEEE 9 and IEEE 39 bus systems, the developed program has been benchmarked with the IRENA FlexTool and the comparisons have been charted out.